2022
DOI: 10.23889/ijpds.v7i1.1713
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the accuracy of data extracted from electronic health records into MedicineInsight, a national Australian general practice database

Abstract: IntroductionMedicineInsight is a database containing de-identified electronic health records (EHRs) from over 700 Australian general practices. Previous research validated algorithms used to derive medical condition flags in MedicineInsight, but the accuracy of data fields following EHR extractions from clinical practices and data warehouse transformation processes have not been formally validated. ObjectivesTo examine the accuracy of the extraction and transformation of EHR fields for selected demographics, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, information on differences between those who did and did not enrol was not available to us. Practice data extracts accurately reflect the data in the source electronic medical records, 24 but the completeness and validity of these data may differ between practices, and we found data harmonisation a problem. Further, the practice data extracts and linked data were not integrated into a single dataset, precluding the inclusion of all variables for propensity score matching and assessment of the relationships between measures of primary care and other health outcomes at the individual level.…”
Section: Discussionmentioning
confidence: 90%
“…However, information on differences between those who did and did not enrol was not available to us. Practice data extracts accurately reflect the data in the source electronic medical records, 24 but the completeness and validity of these data may differ between practices, and we found data harmonisation a problem. Further, the practice data extracts and linked data were not integrated into a single dataset, precluding the inclusion of all variables for propensity score matching and assessment of the relationships between measures of primary care and other health outcomes at the individual level.…”
Section: Discussionmentioning
confidence: 90%
“…The most common method to assess accuracy in healthcare involves the comparison of EHR data to a reference gold standard, which may include paper records, manual data reviews, triangulation of data from multiple sources, or interviews with patients [22]. Measurement of data accuracy can identify issues such as lack of specificity or precision [33]. Previous work found that code precision can be related to staff training and/or use of multiple EHR systems [33][34][35][36].…”
Section: Data Quality Theorymentioning
confidence: 99%
“…Measurement of data accuracy can identify issues such as lack of specificity or precision [33]. Previous work found that code precision can be related to staff training and/or use of multiple EHR systems [33][34][35][36]. As Cook et al [37] noted in a review of DQ issues affecting social determinants data, imprecise codified data may affect minority groups disproportionately, which in turn may affect secondary research outcomes.…”
Section: Data Quality Theorymentioning
confidence: 99%